Family Values and Verbal Bullying among Secondary School Adolescents in Uyo Local Education Committee - Udoh, Gertrude Jeremiah (Jurnal Kajian Bimbingan dan Konseling, 2024)
This study was to determine the relationship between family values and verbal bullying among secondary school adolescents in Uyo Local Education Committee. Two research questions were raised, and two hypotheses formulated and tested at .05 level of significant. A correlational survey design was adopted while the population of the study comprised all 6,613 senior secondary Two (SS2) students in the fifteen (15) public secondary schools in the study area. A sample size of 378 senior secondary two (SS2) was selected for the study using Taro Yamane sampling formulae. To get adequate sampled schools, balloting method of random sampling was used to select 9 public secondary schools out of 15. Thereafter, 42 students were selected from each of the sampled schools using the same random sampling method for instrument administration. The researchers’ structured questionnaire titled “Family Values and Verbal Bullying among Secondary School Adolescents Questionnaire (FVVBSSAQ)” was used for data collection, with reliability co-efficient of .72 and .85 respectively for the independent and dependent variables, using Cronbach Alpha statistics. Data generated from the field was analyzed using Pearson Product Moment Correlation (PPMC) statistics, and the study findings revealed a very low negative and insignificant relationship between mutual respect, tolerance, and verbal bullying secondary school adolescents. Conclusion was drawn from the findings while the research recommended among other things that, parents should cultivate the attitude of mutual respect in the family by addressing members with a polite, cheerful, and amiable voice so that young ones can speak to others with dignity and respect while in school.